Contractual Liability dalam Perjanjian Keagenan Gas Elpiji Non-Public Service Obligation - Ricky Kusnadi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2020)
Pertamina as a producer (principal) sells products to consumers through agents, causing Pertamina not to deal directly with consumers, so there is no contractual liability between producers and consumers. The problem formulation in these studies is: 1) What is the legal relationship between principal and agent based on the Agency Agreement LPG Gas Non-PSO?; 2) What is the contractual liability based on the Agency Agreement LPG Gas Non-PSO?. This type of research is juridical normative with a legal approach and presented in the form of legal interpretation. Agency agreements between principals and agents are not specifically regulated in the KUH Perdata and KUHD, but the principle of freedom of contract allows for an Agency Agreement. The Agency Agreement made between Pertamina and Agent creates a legal relationship that is reflected in the rights and obligations of each party which if not fulfilled is an act of default. Contractual liability refers to legal liability in an agreement / contract. Pertamina gives a gradual sanction to agents. Agents are not permitted to change the selling price and reduction of the tube contents to consumers, so that if a consumer lawsuit occurs, Pertamina is freed from the demands of a third party. As long as the subject matter of the law is contrary to matters that are objects of law, then the case can be criminalized. Every act of a legal subject that is contrary to other legal subjects will become the realm of civil matters.